Study on optical nonlinearity and optical limiting property of porphyrin-oxygenated carbon nanomaterial blends - 温浩 张校亮 刘智波 鄢小卿 李晓春 田建国 (Optoelectronics letters, 2015)
Stable porphyrin-oxygenated carbon nanomaterial dispersions were prepared by blending porphyrin solutions with hy- droxyl groups modified multi-walled carbon nanotubes （MWNTs-OH） and graphene oxide （GO） dispersions, respectively. Optical nonlinearity and optical limiting （OL） property of these blends are investigated in nanosecond regime. Results show that the OL performance of the blends can be tuned by changing the concentrations ratio of porphyrin and oxygenated carbon nanomaterials. The high concentration of oxygenated carbon nanomaterial leads to the poor OL performance. However, with the moderate concentration, the blends exhibit the low threshold value of OL and the en- hanced OL performance at high fluence region. The superior OL performance can be attributed to complementary mechanisms and possible photoinduced electron or energy transfer between porphyrin moiety and oxygenated carbon nanomaterials.